Foot orthoses: how much customisation is necessary? - Menz Hylton B (Journal of Foot and Ankle Research, 2009)
Abstract The relative merit of customised versus prefabricated foot orthoses continues to be the subject of passionate debate among foot health professionals. Although there is currently insufficient evidence to reach definitive conclusions, a growing body of research literature suggests that prefabricated foot orthoses may produce equivalent clinical outcomes to customised foot orthoses for some conditions. Consensus guidelines for the prescription of customised foot orthoses need to be developed so that the hypothesised benefits of these devices can be thoroughly evaluated.